Determinants of Jordanian foreign direct investment inflows: Bounds testing approach - Bekhet H.A. (Elsevier, 2023)
This study aims to evaluate the long-run and short-run relationships among foreign direct investment (FDI) inflows and their determinants in Jordan for the (1978-2012) period. The bounds testing approach is used to analyze the long-run and short-run relationships among the variables. However, the Granger causality test is utilized to explore the directions of causality among the variables. The results identify that there are long-run and short-run relationships among FDI and its determinants. Moreover, the Granger causality test recommends a deferent causal relationship among FDI and their determinants. In general, the Jordanian policy makers have to be aware to the importance of inward FDI in the Jordanian economy. 2015 Elsevier B.V..